Digital Health Utilisation in Nigeria: A Scoping Review - Onumajuru , Hugo Davy; Hayhoe, Richard; Kabir, Russell; Syed, Haniya Zehra (Queeva Publishing, 2024)
Background: The widespread use of mobile phones and technologies in Nigeria presents a unique opportunity that the country can take advantage of in improving access to healthcare. However, evidence on digital health utilization among Nigerians is limited. Therefore, a scoping review was conducted using the PCC (Population, Concept, Context) framework, under the Joanna Briggs Institute guidelines, in which a systematic mapping of available evidence on digital health utilization by patients and healthcare professionals in Nigeria was carried out. Methods: The databases PubMed, CINAHL and MEDLINE with full text via EBSCOhost were thoroughly searched for relevant peer-reviewed articles from the inception of digital health technology until October 2023. Using the eligibility criteria as reference, abstracts and full-texts of 170 articles were screened and 13 records were ultimately selected for the review. Results: Of the 13 included articles, six provided evidences on digital health utilization by health professionals and seven provided evidences on digital health utilization by patients. Patients were enthusiastic about digital health use but the cost of owning a mobile phone was an important barrier. Health professionals had mixed feelings about digital health utilization; whereas perceived usefulness of the technology was an important motivator, lack of computer literacy was an important barrier. Conclusion: The study shows that there is limited published research on digital health utilization in Nigeria. Crucially, very little has been studied about what impact concerns about patient data privacy and safety have on digital health utilization in Nigeria. Further primary research on the motivators of and barriers to digital health utilization by healthcare workers and patients in Nigeria is recommended.